Trichinella pseudospiralis in a wolverine (Gulo gulo) from the Canadian North - Sharma, Rajnish; Thompson, Peter; Elkin, Brett; Mulders, Robert; Branigan, Marsha; Pongracz, Jodie; Wagner, Brent; Scandrett, Brad; Hoberg, Eric; Rosenthal, Benjamin; Jenkins, Emily (DigitalCommons@University of Nebraska - Lincoln, 2019)
Species of Trichinella are a globally distributed assemblage of nematodes, often with distinct host ranges, which include people, domestic, and wild animals. Trichinella spp. are important in northern Canada, where dietary habits of people and methods of meat preparation (drying, smoking, fermenting as well as raw) increase the risk posed by these foodborne zoonotic parasites. Outbreaks in the arctic and subarctic regions of Canada and the United States are generally attributed to T. nativa (T2) or the T6 genotype, when genetic characterization is performed. We report the discovery of Trichinella pseudospiralis (T4), a non-encapsulated species, in a wolverine (Gulo gulo) from the Northwest Territories of Canada. This parasite has been previously reported elsewhere from both mammals and carnivorous birds, but our findings represent new host and geographic records for T. pseu- dospiralis. Multiplex PCR and sequencing of fragments of Cytochrome Oxidase Subunit I (COI) and D3 rDNA confirmed the identification. Phylogenetically, Canadian isolates linked with each other and others derived from Palearctic or Neotropical regions, but not elsewhere in the Nearctic (continental USA). We suggest that mi- gratory birds might have played a role in the dispersal of this pathogen 1000's of km to northwestern Canada. Wolverines are not typically consumed by humans, and thus should not pose a direct food safety risk for tri- chinellosis. However, the current finding suggests that they may serve as an indicator of a broader distribution for T. pseudospiralis. Along with infection risk already recognized for T. nativa and Trichinella T6, our observa- tions emphasize the need for further studies using molecular diagnostics and alternative methods to clarify if this is a solitary case, or if T. pseudospiralis and other freeze susceptible species of Trichinella (such as T. spiralis) circulate more broadly in wildlife in Canada, and elsewhere.